The Influence of Brand Image and Customer Experience on Purchase Decision in Artisan Bakery Industry - Ali, Alvin; Rachman, Adryan; Efawati, Yen (Asosiasi Ahli Administrasi Indonesia, 2026)
This study examines the influence of brand image and customer experience on purchase decisions in the artisan bakery industry, with a case study of Rosella Bakehouse. The growing transformation of bakery products into lifestyle-oriented goods has intensified competition, requiring firms to strengthen both branding and experiential strategies. A quantitative approach was employed using survey data from 150 customers who had prior purchasing experience. Data were analyzed using multiple linear regression. The results reveal that both brand image and customer experience have a positive and significant effect on purchase decisions, with customer experience demonstrating a stronger influence. The model explains 51.8% of the variance in purchase decisions. These findings highlight the critical role of integrating brand positioning with experiential marketing strategies to enhance consumer engagement and purchasing behavior. This study contributes to the literature by providing empirical evidence from a developing market context, particularly within the premium bakery sector.